The influence of tax fahrians and Truth of government oncom bliance behavior: goal commitment as intervening variable - Muslichah, Muslichah (Akutansi Bisnis & Manajemen ( ABM ), 2006)
deskripsi eksperiment the direct and indirect effect of text variance and trust to government on Individual text player complain. In Malang, Des Java titik the respondence of the study are individual text player working in service Industries 53 teks players participate in this study titik disude of the study suggested: (1) the direct effect of trust to government on complain behavior is in significan(2) The index effect Of Truth to government on complain behavior.komitment is in signifikan (3) The direct effect of text varians of compliance behavior it's positive and signifikan (4) The indirect effect of task varians on complain behavior truth commitment is positive and significant